Beyond Point Measurements: Sea Ice Floes Characterized in 3‐D. (12th February 2013) - Williams, Guy D.; Maksym, Ted; Kunz, Clayton; Kimball, Peter; Singh, Hanumant; Wilkinson, Jeremy; Lachlan‐Cope, Tom; Trujillo, Ernesto; Steer, Adam; Massom, Rob; Meiners, Klaus; Heil, Petra; et al.
Abstract : A new methodology for coincident floe‐scale measurements of the surface elevation, snow depth, and ice draft (the thickness below the water line) of Antarctic sea ice has been demonstrated during two recent research voyages: the Australian‐led Sea Ice Physics and Ecosystem Experiment II (SIPEX II) to East Antarctica in September–November 2012 and the United Kingdom–led Ice Mass Balance in the Bellingshausen Sea (ICEBell) voyage to the Weddell and Bellingshausen Seas in November 2010 (Figure 1a).